Một phát hiện mới về địa chất tại Sơn La - Chương, Văn Đức; Thôn, Nguyễn Thế; Thắng, Trần Văn; Việt, Lê Triều; Linh, Phan Doãn; Tùng, Văn Đức (Vietnam Journal of Earth Sciences, 2002)
New discovery of geology in Sonla